Edumath: ADDIE-Based Interactive Media for Improving Fifth-Grade Students' Critical Thinking in Plane Geometry - Devi Mahardika Damayanti; Achmad Buchori; Joko Sulianto (Jurnal Pendidikan Terapan, 2026)
Purpose: Edumath interactive media was developed to evaluate its validity, practicality, and effectiveness in improving fifth-grade students' critical thinking in plane geometry, addressing the limited empirical evidence on systematically developed and evaluated interactive media for elementary geometry learning. Methods: A Research and Development approach employed the ADDIE model and a quasi-experimental nonequivalent control group pretest–posttest design. Participants included 59 fifth-grade students (30 experimental and 29 control). Data were collected through expert validation sheets, teacher and student response questionnaires, and critical thinking tests. Subject-matter, media, and learning experts evaluated the product. Data were analyzed using descriptive statistics, reliability testing, t-tests, and normalized gain (N-gain). Findings: Edumath achieved an average validity score of 88.67%, based on evaluations from the subject-matter expert (89%), media expert (87%), and learning expert (90%), indicating high validity. Teacher and student responses reached 90% and 89%, respectively, demonstrating high practicality. The critical thinking instrument included eight valid essay items with a Cronbach's Alpha of 0.825. The experimental class improved from 18.17 to 26.67, significantly outperforming the control class (t(57) = −8.388, p < .001), and achieved a moderate N-gain (0.63) compared with 0.29 in the control class, confirming Edumath's effectiveness. Research Implications: Edumath provides a valid, practical, and effective digital resource for interactive geometry instruction that strengthens elementary students' critical thinking. Originality: Unlike previous studies examining digital mathematics media separately, ADDIE-based interactive media development was integrated with quasi-experimental evaluation while aligning instructional features with critical thinking indicators in fifth-grade plane geometry learning.